Intravenous Glomus Tumor Masquerading as Lateral Antebrachial Cutaneous Neuroma. (March 2017) - Chim, Harvey; al-Qattan, Husain; Valencia, Herbert; Brathwaite, Carole; Price, Andrew; Grossman, John A. I.
Background: Intravenous glomus tumors are extremely rare.Methods: We report a patient with an intravenous glomus tumor within a venous aneurysm misdiagnosed as a neuroma of the lateral antebrachial cutaneous nerve, based on clinical exam, electrodiagnostic studies, and findings on a magnetic resonance imaging neurogram.Results: After surgical resection, the patient's symptoms, including pain and localized hypersensitivity, totally resolved.Conclusions: This case illustrates 2 important points. First, unlike extradigital glomus tumors, magnetic resonance imaging is not reliable in diagnosing intravenous glomus tumors. Second, in the presence of chronic localized neuroma type pain and sensitivity in the upper limb without a clear cause, an extradigital cutaneous or intravenous glomus tumor must be considered in the differential diagnosis.